Glomerular and tubular C4d depositions in IgA nephropathy: relations with histopathology and with albuminuria - Maeng, Young-In (e-Century Publishing Corporation, 2013)
Background: C4d has been used as an evaluation marker for antibody-mediated rejection for solid organ transplantation. Although some studies have proposed that complement activation is involved in renal diseases, very little information is available on pathogenesis. This study was conducted to investigate C4d deposition in IgA nephropathy and to find its relations with histopathology and albuminuria. Methods: This retrospective study included 23 patients who underwent renal biopsy at our medical center. The WHO grade of IgA nephropathy, interstitial inflammation and fibrosis, C4d staining and medical records including sex, age, and urine albumin were reviewed. Results: Thirteen patients (56.5%) were positive for C4d staining in the glomerulus and eleven patients (47.8%) were positive in the tubular epithelium. Glomerular C4d deposition was associated with albuminuria (p=0.044), and tubular C4d deposition was associated with a higher grade of IgA nephropathy (p=0.014). Conclusions: Activation of the complement system was involved in renal damage and was identified through deposition of C4d in the glomerulus and tubules. Positive C4d staining in the glomerulus and the tubules may be associated with functional damage related to glomerular filtration and poor renal outcome.